BERKARYA UNTUK BANGSA : SINERGISITAS PENGABDIAN KEPADA MASYARAKAT DAN EDUKASI STRATEGI DIGITAL MARKETING DI SOCIETY 5.0 - Abdul Aziz; Muhadi Muhadi; Eka Assolehah Putri (Universitas Bina Bangsa, 2021)
Creative economy entrepreneur in Ragas Masigit Village, Kec. Carenang Kab. Serang is experiencing problems with digital marketing knowledge during the Covid-19 Pandemic towards society 5.0. There needs to be motivation and education that can help creative economy business actors, especially to bounce back from the uncertainty of current conditions. The purpose of this activity is to increase the synergy of community service and explain digital marketing strategies in the era of society 5.0. The types of research used in this research are surveys and case studies with descriptive methods, namely lectures, discussions and mentoring. The material presented at this community service is the pattern of digital marketing strategies in developing the creative economy during the covid 19 pandemic. The result of this activity is that participants can implement comprehensive knowledge of digital marketing strategies and products that are in demand and needed at this time that can create business opportunities. promising